Mineralogical, Geochemical and Isotopic Effect of Silica in Ultramaphic Systems, Eastern Anatolian Turkey - Kilic, Ayse Didem; Inceoz, Murat (Maik Nauka/Interperiodica/Springer, 2015)
Tectonic and hydrogeochemical functions resulted in ophicalcite and listvenite formations thriving throughout tectonic lines in ultramafic rocks in Narman province of Erzurum and Alacakaya province of Elazig. These rocks are most commonly found in serpentinised ultramafites. Serpentine minerals thriving in Ophicalcites (lizardite, chrysotile) and talc, diopside and chromite accompanying these minerals indicate a peridotitic origin, the presence of fluid in the environment and a high reaction rate. In the mineral paragenesis of listvenites and ophicalcites determined by XRD method, quartz + dolomite, dolomite + calcite + quartz, dolomite + quartz + magnesite are mainly determined. In the serpentinised ultramafic rocks, serpentine + magnesite, magnesite + talc and finally magnesite + quartz formations show the change in the thermodynamical conditions (pH, reduction, permeability) and the activity of silica. Encircling such minerals as olivine and lizardite/chrysotile determined by mineralogical examinations, calcite, chlorite, iddingsite and hematite zones indicate progressing metamorphism conditions, the changes occurring in Mg-silicates with the effect of fluids rich in Ca and CO2 and the formation of carbonate. Isotopic studies of delta C-13/C-12 and delta O-18/O-16 ratios of calcite from carbonates and breccia matrix are typical of hydrothermal deposits and serpentinite-carbonate metasomatites. As a result of microscopic examinations, and chemical and isotopic analyses, it can be seen that tectonism, carbonate activity thriving with the hydrothermal functions of medium or low temperature and the progressive metamorphism are effective in the formation of ophicalcites thriving in the ultramafics; the alterations of silicification-carbonatisation type thriving with the metasomatic functions in which the temperature is relatively high are active in the formation of listvenite.
Keywords: Neotethys; ultramafic alteration; ophicalcite; listvenite; trace elements; tectonism